Biomarker data of Core CB1 from the Cygnet Bay, north-western Australia - Zineng Yuan; John K Keesing; Dongyan Liu (PANGAEA, 2022)
The sediment core was collected from a pearl aquaculture area, northwest Australia using a push corer by SCUBA divers in 2011. After collections, the core was sectioned into sub-samples at 1 cm intervals, weighed and freeze dried before being reweighed and then stored in a freezer at -20°C before biomarker analysis. The chronology used 210Pb and 137Cs radiometric-dating techniques, which generated a sedimentation rate of 1.11 cm/yr. The sterol and long chain n-alkane contents were determined by GC (Agilent 7890 A) with an FID detector and a HP-1 column . The GDGTs contents used for calculating TEX86H index were determined by HPLC-MS (Agilent 1200/Waters Micromass-Quattro UltimaTM Pt) with APCI probe and Prevail Cyano Column.